2018
DOI: 10.1016/j.gloplacha.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Drought vulnerability assessment of maize in Sub-Saharan Africa: Insights from physical and social perspectives

Abstract: Drought as a slow-onset phenomenon inflicts important losses to agriculture where the degree of vulnerability depends not only on physical variables such as precipitation and temperature, but also on societal preparedness. While the scopes of physical and social vulnerability are very different in nature, studies distinguishing these two aspects have been lacking. In this study we address the physical and social aspects of drought vulnerability of maize (CDVI phy and CDVI soc) in Sub-Saharan Africa (SSA). To q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Five classifications could be defined between 0 and 1: wet, near normal, mild to moderate drought, severe to extreme drought, and exceptional drought (Svoboda et al 2002) (table 2). More details on the procedure to calculate DEI are explained in Kamali et al (2018b). Different probability distribution functions can be fitted to P and PCP-PET.…”
Section: Components Of Crop Drought Vulnerabilitymentioning
confidence: 99%
“…Five classifications could be defined between 0 and 1: wet, near normal, mild to moderate drought, severe to extreme drought, and exceptional drought (Svoboda et al 2002) (table 2). More details on the procedure to calculate DEI are explained in Kamali et al (2018b). Different probability distribution functions can be fitted to P and PCP-PET.…”
Section: Components Of Crop Drought Vulnerabilitymentioning
confidence: 99%
“…Conversely, the benefits of ambitious mitigation strategies could be annihilated by socioeconomic pathways comparable to the ones depicted in SSP3EU or in SSP4EU. This ability of varying levels of socioeconomic development to reduce (or increase) future heat-related challenges is due primarily to their impact on vulnerability -changes in population exposure being only of secondary importance -, confirming recent results in the field of hunger risk in which social vulnerability plays a major role (Davenport et al, 2017;Kamali et al, 2018). We therefore emphasize here that socioeconomic development pathways should not be viewed solely as potential means to reach a given level of radiative forcing, but also as key determinants of future climate risks, particularly when considering their impact on future populations' vulnerability -and not only on exposure.…”
Section: Resultssupporting
confidence: 75%
“…This con- socioeconomic factors that can enhance or reduce vulnerability of a system or country to climate change and variability. Several studies have reported that socioeconomic factors must be considered when analysing vulnerability to climate change and its extremes (Antwi-Agyei et al, 2012;IPCC, 2014;Kamali et al, 2018). High incidence of poverty is a major contributing factor to vulnerability in many countries in West Africa (Acheampong et al, 2014).…”
Section: Resultsmentioning
confidence: 99%